Complications and management of functional single ventricle patients with Fontan circulation: From surgeon’s point of view - Ma, Jianrui; Chen, Jimei; Tan, Tong; Liu, Xiaobing; Liufu, Rong; Qiu, Hailong; Zhang, Shuai; Wen, Shusheng; Zhuang, Jian; Yuan, Haiyun (Frontiers in Cardiovascular Medicine, 2022)
Fontan surgery by step-wise completing the isolation of originally mixed pulmonary and systemic circulation provides an operative approach for functional single-ventricle patients not amenable to biventricular repair and allows their survival into adulthood. In the absence of a subpulmonic pumping chamber, however, the unphysiological Fontan circulation consequently results in diminished cardiac output and elevated central venous pressure, in which multiple short-term or long-term complications may develop. Current understanding of the Fontan-associated complications, particularly towards etiology and pathophysiology, is extremely incomplete. What’s more, ongoing efforts have been made to manage these complications with the aim to weaken the Fontan-associated adverse impact and improve the life quality, but strategies are ill-defined. Herein, this review summarizes recent studies on cardiac and non-cardiac complications associated with Fontan circulation, focusing on significance or severity, etiology, pathophysiology, prevalence, risk factors, surveillance or diagnosis. From the perspective of surgeons, we also discuss the management of the Fontan circulation based on current evidence, including postoperative administration of antithrombotic agents, ablation, pacemaker implantation, mechanical circulatory support, and final orthotopic heart transplantation, etc., to standardize diagnosis and treatment in the future.